Neurocognitive and Neuropsychiatric Implications of Fibrosing Interstitial Lung Diseases - Zsolt Vastag; Emanuela Tudorache; Daniel Traila; Ovidiu Fira-Mladinescu; Monica Steluta Marc; Cristian Oancea; Elena Cecilia Rosca (Biomedicines)
Patients with interstitial lung diseases (ILDs) associate a large variety of comorbidities that have a significant impact on their clinical outcomes and survival. Among these comorbidities is neurological impairment. This review highlights what is known about the cognitive function, central nervous system (CNS), depression, and anxiety in patients with specific forms of fibrosing ILDs, such as idiopathic pulmonary fibrosis, sarcoidosis, hypersensitivity pneumonitis, connective tissue diseases, etc. The most common pathogenic mechanisms for neurocognitive dysfunction as well as the screening methods and tools for their identification are also described in this review.